2006
DOI: 10.1091/mbc.e05-11-1006
|View full text |Cite
|
Sign up to set email alerts
|

Rad22Rad52-dependent Repair of Ribosomal DNA Repeats Cleaved by Slx1-Slx4 Endonuclease

Abstract: Slx1 and Slx4 are subunits of a structure-specific DNA endonuclease that is found in Saccharomyces cerevisiae, Schizosaccharomyces pombe, and other eukaryotic species. It is thought to initiate recombination events or process recombination structures that occur during the replication of the tandem repeats of the ribosomal DNA (rDNA) locus. Here, we present evidence that fission yeast Slx1-Slx4 initiates homologous recombination events in the rDNA repeats that are processed by a mechanism that requires Rad22 (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 67 publications
8
35
0
Order By: Relevance
“…This is consistent with the interpretation that functions of Rad22 and Rti1 not involved in the repair of Rec12-dependent DNA DSBs do not contribute much to overall spore viability. Such additional functions may involve repair of stalled replication forks in meiotic S phase (Figure 9), consistent with the role of Rad22 in vegetative S phase (Noguchi et al 2004;Coulon et al 2006).…”
Section: Discussionsupporting
confidence: 73%
“…This is consistent with the interpretation that functions of Rad22 and Rti1 not involved in the repair of Rec12-dependent DNA DSBs do not contribute much to overall spore viability. Such additional functions may involve repair of stalled replication forks in meiotic S phase (Figure 9), consistent with the role of Rad22 in vegetative S phase (Noguchi et al 2004;Coulon et al 2006).…”
Section: Discussionsupporting
confidence: 73%
“…In contrast to budding yeast (Flott et al 2007;Li et al 2008), neither slx4Δ nor saw1Δ is sensitive to UV or MMS in fission yeast ( Figure S3 and (Coulon et al 2006). We observed no synthetic growth defects in double mutants between rad16-249 and either slx4Δ or saw1Δ, and little if any effect on MMS or UV sensitivity compared to rad16-249 alone (Table 1 and Figure S3).…”
Section: Rad16-249 Has Genetic Interactions With Other Dna Damage Repmentioning
confidence: 71%
“…Instead, Sc Slx4 and Saw1 are proposed to provide an alternative XPF loading complex, and Slx4 with Slx1 forms another structure-specific endonuclease (Lyndaker and Alani 2009;Schwartz and Heyer 2011). In fission yeast, Slx4-Slx1 endonuclease is linked to rDNA maintenance via a Rad51-independent recombination mechanism (Coulon et al 2006), but so far there is no evidence that Slx4 and Saw1 affect Rad16 XPF in S. pombe. Significantly we and others observe no damage sensitivity in slx4Δ or saw1Δ mutants ( Figure S3 and Coulon et al 2006) and no change in nucleolar morphology in rad16-249 (data not shown), suggesting they operate independently.…”
Section: Genome Instability In Vegetative Rad16 Cellsmentioning
confidence: 99%
“…An important source of spontaneous genomic instability comes from the replication of genomic loci rich in repeated sequences such as the rDNA. In yeast, Slx1-Slx4 maintains the stability of the rDNA locus where it is thought to initiate HR by collapsing stalled replication forks Coulon et al, 2006;Kaliraman and Brill, 2002). It is conceivable that SLX1-SLX4 not only initiates HR by collapsing the stalled fork but also resolves HJs generated after fork recapture.…”
Section: Slx4 Slx1 and Genome Stabilitymentioning
confidence: 99%
“…Slx1 and Slx4, were subsequently shown to be catalytic and regulatory subunits, respectively, of a 5′-flap endonuclease Fricke and Brill, 2003). Studies in S. cerevisiae and S. pombe revealed that Slx1-Slx4 plays a critical role in maintaining the integrity of the ribosomal DNA (rDNA) loci, which are made of tandem rDNA repeats Coulon et al, 2006;Kaliraman and Brill, 2002). Slx1-Slx4 was proposed to initiate DNA recombination by collapsing replication forks stalled at natural replication pause sites.…”
Section: Introductionmentioning
confidence: 99%